2023
DOI: 10.3390/socsci12020085
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Political Debate over the COVID-19 Vaccination on Twitter: Emotions and Polarization in the Spanish Public Sphere

Abstract: In a scenario marked by COVID-19, communication has posed a real challenge for institutions. Since the first case of COVID-19, Spain has faced the enormous challenge of an unprecedented health, economic, and social crisis. The public sphere has put its trust in vaccination as the only chance for the country’s recovery. To determine the role played by political leaders in the debate on vaccination and citizens’ perception of crisis management, this article analyzes the messages posted on Twitter by the four lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The studied time period was established from the first known case of COVID-19 infection in Spain (31/01/2020) and extended for a whole year (31/01/2021). This choice was due to numerous studies confirming that the pandemic led to an exponential increase in disinformation and forced governments to take measures to address the so-called infodemic (Pérez-Dasilva et al, 2020;Salaverría et al, 2020;Pérez-Curiel et al, 2023). The sample universe consists of 1115 interventions that Spanish politicians made in the 65 plenary sessions that took place over a year.…”
Section: Methodsmentioning
confidence: 99%
“…The studied time period was established from the first known case of COVID-19 infection in Spain (31/01/2020) and extended for a whole year (31/01/2021). This choice was due to numerous studies confirming that the pandemic led to an exponential increase in disinformation and forced governments to take measures to address the so-called infodemic (Pérez-Dasilva et al, 2020;Salaverría et al, 2020;Pérez-Curiel et al, 2023). The sample universe consists of 1115 interventions that Spanish politicians made in the 65 plenary sessions that took place over a year.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of discourses surrounding hashtags on Twitter has been applied across various disciplines and for diverse purposes, such as sustainability discourses [46,47], political discourses [48,49] or health and nutrition discourses [45,50,51]. These studies have demonstrated that Twitter data are valuable for gaining insights into perspectives that are often challenging to access and underrepresented in empirical social research.…”
Section: Social Media As a Voice Amplifier For Food Poverty Experiencesmentioning
confidence: 99%
“…Fake news consumption is based on being spread via social media (Baptista and Gradim 2020), which is especially successful when dealing with topics from local and national politics (Pérez-Curiel et al 2023). Local media promote a strong commitment between journalists and citizens, showing a great value to the community (Park 2022).…”
Section: Introductionmentioning
confidence: 99%